Physical and Electrochemical Study of Cobalt Oxide Nano- and Microparticles - Ortiz-Farias, J; Ortiz-Farias, J; Gautier-Zamora, J; Gautier-Zamora, J; Escrig-Murua, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Casagrande-Denardin, J (Elsevier Inc., 2014)
Cobalt oxide nanocrystals of size 17-21 nm were synthesized by a simple reaction between cobalt acetate (II) and dodecylamine. On the other hand, micrometric Co3O4 was prepared using the ceramic method. The structural examination of these materials was performed using powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM and HRTEM). XRD studies showed that the oxides were pure, well-crystallized, spinel cubic phases with a-cell parameter of 0.8049 nm and 0.8069 nm for the nano and micro-oxide, respectively. The average particle size was 19 nm (nano-oxide) and 1250 μm (micro-oxide). Morphological studies carried out by SEM and TEM analyses have shown the presence of octahedral particles in both cases. Bulk and surface properties investigated by X-ray photoelectron spectroscopy (XPS), point zero charge (pzc), FTIR and cyclic voltammetry indicated that there were no significant differences in the composition on both materials. The magnetic behavior of the samples was determined using a vibrating sample magnetometer. The compounds showed paramagnetic character and no coercivity and remanence in all cases. Galvanostatic measurements of electrodes formed with nanocrystals showed better performance than those built with micrometric particles. © 2014 Elsevier Inc.